The relationship between Social Security Administrator (BPJS) regulations and the value of benefits obtained by Social Security Administrator for Employment (BPJS Ketenagakerjaan) participants - Sistiaperdani, Resly; Zubaedah, Cucu; Wardani, Riana; Hayati, Ayu Trisna; Carolina, Dyah Nindita (Universitas Padjadjaran, 2020)
Introduction: One of the human rights is the right to live prosperously. Indonesian government provides social security for workers, namely the Social Security Administrator for Employment (BPJS Ketenagakerjaan). Social Security Administrator for Employment has a specific set of regulations set by the government. Social Security Administrator for Employment participants obtains the value of benefits through the social security program. This study was aimed to analyse the relationship between regulations and the value of benefits obtained by BPJS Employment participants. Methods: This research was a correlational descriptive study with a survey method. Results: Most respondents stated strongly agree with the regulations of Social Security Administrator for Employment (85.09%), and most respondents felt that they gained a lot of the value of benefits as expected (83.80%). The results of the Spearman correlation test between the Social Security Administrator for Employment regulations with the values obtained by respondents, which resulted in p = 0.0001 with α = 0.05. The p-value that lower than the α indicates a significant relationship. Conclusion: There is a relationship between the regulations of Social Security Administrator for Employment and the values obtained for the participants, with the direction of positive correlation and the moderate correlation strength.